2014
DOI: 10.3389/fnhum.2014.00395
|View full text |Cite
|
Sign up to set email alerts
|

Music mnemonics aid Verbal Memory and Induce Learning – Related Brain Plasticity in Multiple Sclerosis

Abstract: Recent research on music and brain function has suggested that the temporal pattern structure in music and rhythm can enhance cognitive functions. To further elucidate this question specifically for memory, we investigated if a musical template can enhance verbal learning in patients with multiple sclerosis (MS) and if music-assisted learning will also influence short-term, system-level brain plasticity. We measured systems-level brain activity with oscillatory network synchronization during music-assisted lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 89 publications
(110 reference statements)
2
31
0
2
Order By: Relevance
“…Additionally, the amusic and the memoryimpaired subjects showed an advantage of sung over spoken task performance in delayed recall (memory-impaired subjects also in the second learning trial) at the 6-month stage. In general, the positive mnemonic effects of the sung stories observed here in all patient subgroups are in line with similar findings from previous studies of persons with MS 25 and AD. [26][27][28] At the neural level, these effects are most likely related to the bilaterality of the temporal, frontal, and limbic networks engaged in processing songs [45][46][47] and to the preservation of vocal music processing in spared brain regions previously reported in amusia and aphasia after stroke using fMRI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, the amusic and the memoryimpaired subjects showed an advantage of sung over spoken task performance in delayed recall (memory-impaired subjects also in the second learning trial) at the 6-month stage. In general, the positive mnemonic effects of the sung stories observed here in all patient subgroups are in line with similar findings from previous studies of persons with MS 25 and AD. [26][27][28] At the neural level, these effects are most likely related to the bilaterality of the temporal, frontal, and limbic networks engaged in processing songs [45][46][47] and to the preservation of vocal music processing in spared brain regions previously reported in amusia and aphasia after stroke using fMRI.…”
Section: Discussionsupporting
confidence: 93%
“…), very little is yet known about the potential mnemonic effects of songs for learning and recall of novel verbal material in neurological patients. An advantage of sung material over spoken material has previously been observed in the learning and recall of word lists in multiple sclerosis (MS) patients, as well as in the recognition of unfamiliar song lyrics in Alzheimer's disease (AD) patients . To date, only two studies have assessed the learning of unfamiliar song lyrics in stroke patients with chronic aphasia .…”
Section: Introductionmentioning
confidence: 99%
“…As motivational processes directly impact knowledge acquisition and transfer, it would seem that the integration and usage of the iPad® in educational and therapeutic environments should be further explored (Wang, Teng, & Chen, 2015 Care providers often utilize music for social and academic skill attainment (Brownell, 2002;Schwartzberg & Silverman, 2013). Researchers have used melody to assist with the immediate recall of information for individuals with neurologic disabilities (Schwartzberg & Silverman, 2012;Thaut, Peterson, McIntosh, & Hoemberg, 2014). McElhinney and Annett (1996) concluded that there was a better overall recall of familiar words correctly recalled in a song condition than in a reading condition.…”
Section: Non-music Ba Non-music Based Appr Sed Appro Oaches T Aches Tmentioning
confidence: 99%
“…Liking the music is, therefore, one major aspect when seeking positive effects from its listening. Among many other effects, major higher cognitive functions positively affected by music include reading and literacy skills [33], working memory and mathematical abilities [34], memory [35] or concentration and attention [36].…”
Section: The Effects Of Musicmentioning
confidence: 99%